2014
DOI: 10.4054/demres.2014.30.54
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes on marriage and new relationships

Abstract: BACKGROUNDConsistent with the deinstitutionalization-of-marriage thesis, studies report a decline in support for marital conventions and increased approval of other relationship types. Generalizations are limited by the lack of cross-national research for a broad domain of attitudes on marriage and alternative arrangements, and by the lack of consensus on what counts as evidence.OBJECTIVEAcknowledging the conceptual distinction between expectations for behavior inside and outside marriage, we address the deins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…Alongside a greater acceptance of gay men and lesbian women (Keleher & Smith, 2012), liberal attitudes toward sexuality have resulted in a fundamental shift in societal perception of and rationale for sexual intercourse (Treas, Lui & Gubernskaya, 2014). No longer viewed as primarily for procreation, there is a focus on the recreational and pleasurable aspects of sex instead (Twenge et al, 2015).…”
Section: Sex In a Sexualized Societymentioning
confidence: 99%
“…Alongside a greater acceptance of gay men and lesbian women (Keleher & Smith, 2012), liberal attitudes toward sexuality have resulted in a fundamental shift in societal perception of and rationale for sexual intercourse (Treas, Lui & Gubernskaya, 2014). No longer viewed as primarily for procreation, there is a focus on the recreational and pleasurable aspects of sex instead (Twenge et al, 2015).…”
Section: Sex In a Sexualized Societymentioning
confidence: 99%
“…In particular, cross-national studies on family attitudes, such as attitudes toward marriage and cohabitation (Aassve, Sironi, & Bassi, 2013;Treas et al, 2014;Yucel, 2015) or the acceptance of homosexuality (Hooghe & Meeusen, 2013;Lottes & Alkula, 2011;van den Akker et al, 2013), have shown the importance of understanding individual variation in attitudes within differing national contexts. For example, Treas et al (2014), by using pooled country data for 21 industrialized countries to analyze the decline in disapproval of alternatives to marriage (cohabitation, unmarried parents, and premarital and gay and lesbian sex), found that individual-level characteristics such as gender and age were important determinants of these attitudes, yet significant cross-country differences remained. Similarly, Gubernskaya (2010), when investigating changing attitudes toward family formation in relation to both individual and country-level characteristics, concluded significant cross-country variation in attitudes remains unexplained once controlling for gender, educational level, employment status, marital status, and religiosity (frequency of attendance).…”
Section: Previous Researchmentioning
confidence: 99%
“…On the one hand, the large body of research focusing on attitudes toward the redistributive role of the welfare state (e.g., Raven, Achterberg, van der Veen, & Yerkes, 2011;Sachweh & Olafsdottir, 2012;van Oorschot, 2007;Wright & Reeskens, 2013) does not address social rights connected to living in diverse family forms. On the other hand, the various studies focusing on attitudes toward homosexuality (e.g., Hooghe & Meeusen, 2013;Kuntz, Davidov, Schwartz, & Schmidt, 2015;Kuyper et al, 2013;Takács & Szalma, 2013;van den Akker, van der Ploeg and Scheepers, 2013) or marriage and alternative forms of family formation (Treas, Lui, & Gubernskaya, 2014) have tended to address the general acceptance of "diverse family forms" or "diverse individuals" without addressing the issue of citizenship rights attached to this diversity. Exceptions to this include studies providing insights into attitudes toward the rights of same-sex couples in the United States (Doan, Loehr, & Miller, 2014;Miller & Chamberlain, 2013), Portugal (Costa et al, 2014), and Sweden and Norway (Jakobsson, Kotsadam, & Jakobsson, 2013).…”
mentioning
confidence: 99%
“…Marriage remains but becomes a marker of status and recognition for individuals, and as such is notably incapable of being evaluated in terms of its institutional significance. Thus, in many ways the valuation and practice of marriage may appear to remain somewhat constant, but its internal core and meaning has shifted in historically unprecedented ways (Coontz, 2005;Finkel, Hui, Carswell, & Larson, 2014;Lewin, 2004;Treas, Lui, & Gubernskaya, 2014). Deinstitutionalization scholars have also emphasized how similar changes, though perhaps not as fully developed, are transforming parent-child and other familial relations (Blankenhorn, 1995;Dizard & Gadlin, 1992;Edwards et al, 2012;Gillies, 2011;Rosenfeld, 2007).…”
Section: Diversification: Theorizing Family In Postinstitutional Termsmentioning
confidence: 99%